1999
DOI: 10.1046/j.1460-2695.1999.t01-1-00185.x
|View full text |Cite
|
Sign up to set email alerts
|

Gigacycle fatigue of ferrous alloys

Abstract: The objective of this paper is to determine the very long fatigue life of ferrous alloys up to 1 × 1010 cycles at an ultrasonic frequency of 20 kHz. A good agreement is found with the results from conventional tests at a frequency of 25 Hz by Renault between 105 and 107 cycles for a spheroidal graphite cast iron. The experimental results show that fatigue failure can occur over 107 cycles, and the fatigue endurance stress Smax continues to decrease with increasing number of cycles to failure between 106 and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…Wang et al. 18 measured the temperature during high frequency tests by a thin thermocouple attached to the specimen surface at the center section. They identify two zones in the temperature versus cycles’ curves during the VHCF test: Stage I, where a steep rise in temperature occurs up to 10 6 cycles, attaining a maximum temperature which depends on the vibration amplitude; Stage II, where the curve saturates and is almost horizontal.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al. 18 measured the temperature during high frequency tests by a thin thermocouple attached to the specimen surface at the center section. They identify two zones in the temperature versus cycles’ curves during the VHCF test: Stage I, where a steep rise in temperature occurs up to 10 6 cycles, attaining a maximum temperature which depends on the vibration amplitude; Stage II, where the curve saturates and is almost horizontal.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that frequency effect was much more significant between 0.001 and 10 Hz than between 10 and 20,000 Hz. The insignificant influence of loading frequency was also reported in ferrous-type alloy [6] and nonferrous metals [7,8]. Tridello, Paolino, et al [9][10][11][12] evaluated the size effect analytically in the VHCF regime and validated on the full-scale specimen.…”
Section: Introductionmentioning
confidence: 84%
“…It was found that the geometry of the pores at which cracks were initiated had little influence on crack propagation, but in almost all cases, final fracture was originating from a pore at the surface or just below it. Extensive studies on the fatigue properties of various materials ranging from 10 6 to 10 9 cycles have shown that both ferrous and non‐ferrous metals experience failure under long cycling loadings 8–11 . The assumption of infinite fatigue life is mainly attributed to limitations of traditional fatigue testing machines which operate at frequencies of less than 100 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies on the fatigue properties of various materials ranging from 10 6 to 10 9 cycles have shown that both ferrous and nonferrous metals experience failure under long cycling loadings. [8][9][10][11] The assumption of infinite fatigue life is mainly attributed to limitations of traditional fatigue testing machines which operate at frequencies of less than 100 Hz. Fatigue failure is usually induced by the crack initiation and propagation at stress concentrations on the surface of the material for life ranging up to 10 8 cycles.…”
Section: Introductionmentioning
confidence: 99%